Avaliação da acurácia dos rastreadores propostos pelo Institute for Health Care Improvement para identificação de eventos adversos a medicamentos - Maria das Dores Graciano Silva (2017)
Background: Adverse drug events (ADEs) can seriously compromise the safety and quality of care provided to hospitalized patients, requiring the adoption of accurate methods to monitor them. We sought to evaluate the accuracy of the triggers proposed by the Institute for Healthcare Improvement (IHI) for identifying ADEs. Methods: A prospective study was conducted in a large-scale public university hospital, in 2015, with patients 18 years of age or older, from the hospitals medical and surgical clinics. Triggers proposed by IHI and clinical alterations suspected to be ADEs were searched daily reviewing medical records and patient interview. The number of days in which the patient was hospitalized was considered as unit of measure to evaluate the accuracy of each trigger. Results: Three hundred patients were included in this study. Mean age was 56.3 years (standard deviation (SD) 16.0), and 154 (51.3%) were female. The frequency of patients with ADEs was 24.7% and at least one trigger present was 53.3%. Most common ADEs were hypotension (21.2%) and constipation (18.3%), and most frequent triggers were antiemetics (57.5%) and abrupt medication stop (31.8%). Sensitivity of the triggers ranged 0.3-11.8 % and the positive predictive value ranged 1.2-27.3%. Specificity and negative predictive value were greater than 86%. The majority of patients identified by the presence of triggers did not present ADEs (64.4%). In 40 (38.5%) ADEs, the triggers were not present. Conclusions: The triggers did not present good accuracy. We therefore suggest that other strategies must be studied in an attempt to develop an ADEs monitoring practice that can positively impact the quality of medical care and safety provided to hospitalized patients.